Exercise training in patients with a left ventricular assist device (Ex-VAD): rationale and design of a multicentre, prospective, assessor-blinded, randomized, controlled trial - Bobenko, Anna; Schoenrath, Felix; Knierim, Jan H.; Friede, Tim; Verheyen, Nicolas; Mehra, Mandeep R.; Haykowsky, Mark; Herrmann-Lingen, Christoph; Duvinage, Andre; Pieske-Kraigher, Elisabeth; Halle, Martin; Falk, Volkmar; et al. (European Journal of Heart Failure, 2019)
Aims: Left ventricular assist device (LVAD) therapy is a promising option for patients with advanced heart failure (HF), refractory to guideline-mandated medical treatment either as a bridge to heart transplantation or as lifelong therapy. Functional capacity improves after LVAD implantation but remains reduced in patients with long-term LVAD therapy. Exercise training (ET) improves functional capacity and quality of life (QoL) in HF and may provide incremental benefits in patients supported with LVAD therapy. Methods: The primary objective of Ex-VAD is to investigate whether a 12-week supervised ET can improve peak oxygen uptake (peakVO2) measured by cardiopulmonary exercise testing (CPET) on an ergometer. The study is powered to demonstrate a group difference of 3 mL/min/kg in peakVO2 at week 12, with a power of 0.9 and a standard deviation of 5 mL/min/kg. After baseline assessments to determine whether ET is safe, 66 patients at six trial sites with advanced HF and LVAD therapy will be randomized 2:1 to supervised ET or to the control arm of usual care alone. Patients randomized to ET will perform supervised aerobic endurance and resistance ET (three times/week) for 12 weeks. At baseline and during follow-up, anthropometry, CPET, echocardiography (at rest and exercise), and QoL evaluation will be performed. Blood samples will be collected to examine cardiac-specific relevant biomarkers. Overall physical activity, training sessions, and adherence will be monitored and documented throughout the study using accelerometers and patient diaries. Conclusions: The Ex-VAD trial will assess the effects of a supervised ET programme on peakVO2 and QoL in patients with LVAD. As LVAD therapy moves from crisis support to ambulatory functional enhancement, this trial will provide a rationale to improve functional capacity and, in perspective, cardiovascular outcomes in LVAD-supported patients with advanced HF.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Advanced heart failure; Left ventricular assist device; Supervised exercise training